2018
DOI: 10.4103/njms.njms_59_15
|View full text |Cite
|
Sign up to set email alerts
|

Oral squamous cell carcinoma profile in North-Eastern regions of India from habits to histopathology: A hospital-based study

Abstract: Background:Head and neck cancers constitute about 5%–8% of total body cancers in Europe, America, but in India, this figure is somewhat higher. The aim of this study is to evaluate the current burden of oral cancers in India, particularly North-East India.Materials and Methods:A full-length study starting from patient counseling to clinical and histopathological examination and grading was planned. The study was conducted under the guidance of clinician, oral surgeon, oral pathologists, and statistician.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…This is in accordance with several other studies. 3,7,9,10 Men predominated over women with male to female ratio of 5:1. Our findings are similar to several other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with several other studies. 3,7,9,10 Men predominated over women with male to female ratio of 5:1. Our findings are similar to several other studies.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the increased usage of smokeless tobacco in various forms in the Indian subcontinent, where the tobacco quid is kept on the side of the mouth or under the lips for a prolonged period. 9,10,12,13 Most of our patients required some form of mandibular resections so as to ensure R0 resection and negative margins. Our resection rates are comparable to the study done by Shukla et al 14 Pectoralis major myocutaneous (PMMC) was the most common reconstruction option used by us, and there was no incidence of partial or complete flap dehiscence, which shows that it is a robust and sturdy flap, and is a workhorse of resource-constrained settings.…”
mentioning
confidence: 99%
“…also reported the fact that unawareness is a major cause of delayed reporting as most of these patients were illiterate and from lower socioeconomic status. [ 5 ] This delay in rendering treatment to the primary OSCC can lead to nodal metastasis which is associated with poor disease control and reduces overall survival by 30%–50%. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have shown that the incidence of oral cancer is increasing among women due to changes in their habits. [12][13][14] Patients referred were frequently middle-aged or elderly. This result agrees.…”
Section: Discussionmentioning
confidence: 99%